Shallow fluid seepage systems in the Hammerfest Basin and adjacent Fault complex - Tesfay, Yohannes (UiT The Arctic University of Norway, 2015)
This study was carried out using three high resolution 3D P-cable seismic datasets to explore shallow gas distribution and possible fluid migration pathways in the Snøhvit field and Ringvassøy-Loppa Fault Complex. The Snøhvit field situated in the center of the Hammerfest Basin is oil and gas field discovered in 1994. Ringvassøy-Loppa Fault complex marks the border between the Hammerfest and Tromsø Basin. The seismic data cover seabed pockmarks and gas chimney in the Snøhvit field, and a buried pockmark area in the Ringvassøy-Loppa Fault Complex. These features were examined in this these. Bedding planes of early Triassic Clinoforms are understood to have been used as fluid flow pathways by fluids ascending from deeper strata and they terminate under glacial deposits that act as permeability barrier. Enhanced reflections aligned perpendicularly to the dip of the clinoforms are common at the base of the glacial unit. The investigation of pockmarks reveled a close relationship between ice free conditions and fluid flux.